1996
DOI: 10.1677/joe.0.1480319
|View full text |Cite
|
Sign up to set email alerts
|

Identification of epidermal growth factor-secreting cells in the anterior pituitary of lactating female rats

Abstract: Epidermal growth factor (EGF) is synthesized and secreted by mammalian anterior pituitary cells. It stimulates GH and prolactin (PRL) secretion, but the cellular origin of EGF is relatively unexplored. The objective of this study was to characterize the cells that secrete EGF in the anterior pituitary of lactating rats. An EGF reverse haemolytic plaque assay (RHPA) was used to identify EGF-secreting cells and this RHPA was combined with immunofluorescence using antibodies to the six major adenohypophysial horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…In a study by Ren et al [29], relatively few secretory cells were shown to exhibit EGF immunoreactivity in human anterior pituitaries, but their cell type was not determined in that study. The discrepancy in results between the present and previous studies is probably due to differences in animal species used, or physiological states examined, since EGF mRNA synthesis in rat pituitary glands is known to be altered under certain conditions, such as lactation or cold stress [27, 28], or upon treatment with estrogen [16, 27, 30]. These results indicate that somatotropes usually express EGF mRNA in rat and mouse pituitaries, and that EGF may play roles in regulating pituitary functions through the pituitary EGF-EGF receptor system.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In a study by Ren et al [29], relatively few secretory cells were shown to exhibit EGF immunoreactivity in human anterior pituitaries, but their cell type was not determined in that study. The discrepancy in results between the present and previous studies is probably due to differences in animal species used, or physiological states examined, since EGF mRNA synthesis in rat pituitary glands is known to be altered under certain conditions, such as lactation or cold stress [27, 28], or upon treatment with estrogen [16, 27, 30]. These results indicate that somatotropes usually express EGF mRNA in rat and mouse pituitaries, and that EGF may play roles in regulating pituitary functions through the pituitary EGF-EGF receptor system.…”
Section: Discussionmentioning
confidence: 66%
“…Using in situ hybridization and immunocytochemistry, Fan et al [27]revealed that somatotropes and gonadotropes express EGF mRNA in rat pituitaries, and that cold stress induces EGF mRNA expression in corticotropes and thyrotropes. Moreover, a reverse hemolytic plaque assay subsequently demonstrated that EGF is secreted from all types of pituitary secretory cells in lactating rats [28]. In a study by Ren et al [29], relatively few secretory cells were shown to exhibit EGF immunoreactivity in human anterior pituitaries, but their cell type was not determined in that study.…”
Section: Discussionmentioning
confidence: 99%
“…2000). These cells functionally secrete EGF, confirmed on reverse hemolytic plaque assays and IHC of rat anterior pituitary plurihormonal cells (Mouihate & Lestage 1995 a , b , Mouihate et al . 1996 b ).…”
Section: Anterior Pituitary Tissuementioning
confidence: 64%
“…The epidermal growth factor (EGF) family of growth factors is able to modulate the proliferation, secretion and differentiation of most endocrine glands (for review see Fisher & Lakshman 1990). EGF is normally present in the pituitary, where it appears to be produced by subpopulations of all hormone-producing cell types, and especially by gonadotropes and thyrotropes (Kasselberg et al 1985, Mouihate et al 1996. The epidermal growth factorreceptor (EGF-R) is also normally expressed by anterior pituitary cells (Fan & Childs 1995), with EGF binding sites being localized mainly to lactotrope and somatotrope cells (Chabot et al 1986).…”
Section: Introductionmentioning
confidence: 99%